2020
DOI: 10.1108/jrim-11-2018-0155
|View full text |Cite
|
Sign up to set email alerts
|

An international investigation of opinion leadership and social media

Abstract: Purpose This paper aims to examine innovativeness and extraversion as antecedents of perceived and social media opinion leadership in different country-level contexts and explore how these antecedents influence product adoption differently. Design/methodology/approach A survey method was used to collect data from Turkey and the USA. A total of 415 respondents participated in two studies, and data were analyzed using structural equation modeling. Findings This research shows that innovativeness affects perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 76 publications
0
34
0
Order By: Relevance
“…Compared with traditional celebrity endorsement by movie or athletic stars with higher social status, micro influencers or KOLs from ordinary people are more close to the life of an average consumer and capable of becoming more interactive with followers and potential consumers (Al-Emadi and Ben Yahia, 2020). Such real life influencers from the grassroots, who are product innovators and passionate about the recommended products, not only have a significant following but a relatively higher number of buying conversations because consumers are likely to trust and act on a UGC (Akdevelioglu and Kara, 2020). The buying-while-watching function in social media or live streaming platforms let viewers instantly add goods to the shopping cart in interactive live streaming.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional celebrity endorsement by movie or athletic stars with higher social status, micro influencers or KOLs from ordinary people are more close to the life of an average consumer and capable of becoming more interactive with followers and potential consumers (Al-Emadi and Ben Yahia, 2020). Such real life influencers from the grassroots, who are product innovators and passionate about the recommended products, not only have a significant following but a relatively higher number of buying conversations because consumers are likely to trust and act on a UGC (Akdevelioglu and Kara, 2020). The buying-while-watching function in social media or live streaming platforms let viewers instantly add goods to the shopping cart in interactive live streaming.…”
Section: Introductionmentioning
confidence: 99%
“…Internet celebrities have been shown to affect the decisions of their social media followers (Akdevelioglu and Kara, 2020; Al-Emadi and Ben Yahia, 2020). Therefore, investigating the role of Internet celebrities in impulse purchase behavior is of great interest to Internet marketing managers.…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence shows that followers of these celebrities on Internet platforms are prone to impulse buying behavior owing to parasocial relationships (Graham and Wilder, 2020; Styvén et al , 2017; Xiang et al , 2016). Recent literature indicated that Internet celebrities attract various followers through individual characteristics via the cognitive processing mechanism (Akdevelioglu and Kara, 2020; Ferchaud et al , 2018; Vander Schee et al , 2020). Cognitive processing mechanism is when the user assesses the “scent” provided by the link's text or icon, determining whether the link will lead to desired content (Ong et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Correa et al [75] found that extraversion is positively related to social media usage. Akdevelioglu and Kara [76] found that extraversion affects social media opinion leadership. However, previous studies indicated that shy individuals are more likely to use social media platforms [10,55].…”
Section: Discussionmentioning
confidence: 99%
“…Second, and more importantly, by examining the effect of innovativeness, extraversion, and interpersonal relationship competency on opinion leadership propensity in Saudi Arabia, this research has implications for effectively identifying opinion leader dynamics in another context [77]. Examining the personality traits of consumers who engage in social media networking in different contexts is important for marketers, so they can establish segmentation based on cultural characteristics, such as uncertainty avoidance and individualism/collectivism [13,76]. This study also highlights the importance of interpersonal relationship competency and innovativeness in the identification of opinion leaders in Saudi Arabia.…”
Section: Practical Implicationsmentioning
confidence: 99%